Logging in boreal field‐forest ecotones promotes flower‐visiting insect diversity and modifies insect community composition. Issue 2 (3rd October 2014) - Korpela, Eeva‐Liisa; Hyvönen, Terho; Kuussaari, Mikko; Leather, Simon R.; Packer, Laurence
Abstract Mitigation tools aimed at counteracting the loss of farmland insect diversity and associated ecosystem services are usually conducted on cultivated fields. Possibilities of managing field‐forest ecotones for biodiversity have been rarely discussed, despite their importance for flower‐visiting insects. The effectiveness of logging in enhancing three aspects of insect diversity (bumblebee abundance, total species richness, and habitat specialist butterfly abundance) and changes in insect community composition were studied in a three‐year field experiment. The study included 15 field‐forest ecotones, each with a 50 m long and 25 m wide treated area and a corresponding control. At forest edge, a 5 m wide strip was clear‐cut and behind this strip, a 20 m wide belt was thinned to a basal area of 8 m2 ha−1. Logging simultaneously promoted all three aspects of insect diversity. Changes were more apparent at clear‐cut edge than in the thinned interior. Community composition changed via increased abundance of open habitat species, especially butterflies. Logging promoted warm microclimates and flower availability at clear‐cut edges. All three aspects of insect diversity showed a positive response to flower coverage, which in turn was negatively correlated with the amount of logging residue. Creating open field‐forest ecotones is beneficial for flower‐visiting insects and open habitat species in particular. This approach is expected to be most beneficial at sunny forest edges and sites which become overgrown slowly. In addition, we suggest logging residue to be removed when aiming to promote flower‐visitors.